General relativistic quantum optics: Finite-size particle detector models in curved spacetimes - Martin-Martinez, Eduardo; Rick Perche, T. [UNESP]; Torres, Bruno de S. L. [UNESP] (Amer Physical Soc, 2020)
We propose a fully covariant model for smeared particle detectors in quantum field theory in curved spacetimes. We show how effects related to accelerated motion of the detector and the curvature of spacetime influence the way different observers assign an interaction Hamiltonian between the detector and the field. The fully covariant formulation explicitly leaves the physical predictions of the theory invariant under general coordinate transformations, hence providing a description of particle detector models (e.g., Unruh-DeWitt detectors, models for the light-matter interaction, etc.) that is suitable for arbitrary trajectories in general spacetime backgrounds.